Model Pembelajaran Bahasa Inggris Berbasis Kumon untuk Meningkatkan Kemampuan Reading Mahasiswa - Oktariyani, Oktariyani; Oktariyana, Oktariyana (STKIP PGRI Bandar Lampung, 2020)
This study aims to develop and test the effectiveness of a product in the form of a Kumon-based English learning model. This research uses qualitative and quantitative approaches. While the research method used in this study is a research and development method which adopts the theory of Borg and Gall. This research has produced a product in two forms, namely Kumon-based reading learning books and audio. Based on the results of the effectiveness test of the Kumon-based learning model of English, it is proven that there is a significant difference (meaning) between before and after being given the Kumon-based learning model. This can be seen from the results in the significant difference test obtained by mean = 0.220, indicating the difference between the pretest and posttest results, the results of t-count = 9.465, with db = 29 and p-value = 0.224 ≥ 0.05, which means that there is a significant difference. Significant between before and after being given the Kumon-based English learning model treatment. So thus the Kumon-based English learning model that has been developed is better than the previous learning model.